STUDI TENTANG KEPUTUSAN MENABUNG DI BANK SYARIAH (KASUS PADA NASABAH BANK BJB SYARIAH) - Ika Octaviani, - (2020)
Based on sharia bank market share data only reached 5.9%. This indicates that the sharia bank has not been the main choice for Indonesian people to fulfill their needs both to save and obtain financing assistance. Whereas the majority of Indonesians are Muslims who need financial institutions that do not contradict the conduct of Islamic law. Decisions made by Muslim customers must be based on the halal and Haram paradox. This research aims to analysts to the extent that the influence of quality of service and religiusity to the decision of saving in Sharia bank (case on customers of Bank BJB Syariah). This research uses primary data. The research method used is a descriptive method of causality with multiple linear regression analyses. The population in this study of savings customers in BJB Syariah Bank Braga Branch office amounted to 4,129 with samples amounting to 100. The dependent variable in the study is a decision to save in Sharia banks. Furthermore, independent variables in research are quality of service and religiusity. Based on the results of the research known positive and significant service quality to the decision of saving in Sharia banks. While Religiusity has a positive and significant effect on the decision to save in Sharia banks. The quality of service and religiality simultaneously influence positive and significant to the decision of saving in Sharia banks. Keywords : Decision Saving, Quality of Service, Religiusity, Multiple Linear Regression.